2001
DOI: 10.1242/dev.128.23.4899
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping functions of lysosomal acid phosphatase (LAP) and tartrate-resistant acid phosphatase (Acp5) revealed by doubly deficient mice

Abstract: To date, two lysosomal acid phosphatases are known to be expressed in cells of the monocyte/phagocyte lineage: the ubiquitously expressed lysosomal acid phosphatase (LAP) and the tartrate-resistant acid phosphatase-type 5 (Acp5). Deficiency of either acid phosphatase results in relatively mild phenotypes, suggesting that these enzymes may be capable of mutual complementation. This prompted us to generate LAP/Acp5 doubly deficient mice. LAP/Acp5 doubly deficient mice are viable and fertile but display marked al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Therefore, we tested whether accumulation of HER2-HApt-AuNS complexes in lysosomes affected lysosomal activity by comparing the levels of lysosomal marker enzymes. 54 We measured acid phosphatase, an acid hydrolase commonly in lysosomes, 55 from cell-cultured media and cell lysates after 24 h incubation of free HApt and HApt-AuNS. The assay demonstrated that HApt-AuNS induced a 1.5 ((0.2) times increase of acid phosphatase levels in cells compared to free HApt.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tested whether accumulation of HER2-HApt-AuNS complexes in lysosomes affected lysosomal activity by comparing the levels of lysosomal marker enzymes. 54 We measured acid phosphatase, an acid hydrolase commonly in lysosomes, 55 from cell-cultured media and cell lysates after 24 h incubation of free HApt and HApt-AuNS. The assay demonstrated that HApt-AuNS induced a 1.5 ((0.2) times increase of acid phosphatase levels in cells compared to free HApt.…”
Section: Resultsmentioning
confidence: 99%
“…However, all ACP4 orthologs do not have the critical tyrosine of “YXXØ” motif or other known lysosome sorting signals, suggesting that ACP4 is primarily not a lysosomal protein. Moreover, in the Acp4 R110 C/R110C mouse incisor, secretory stage ameloblasts do not show significantly enlarged lysosomes, which are commonly seen in specific cells of mice lacking one of the lysosomal acid phosphatases, including ACP2, ACP3, and ACP5 66 , 67 . Collectively, all these pieces of evidence indicate that ACP4 probably does not function as a lysosomal degradative enzyme during enamel formation.…”
Section: Discussionmentioning
confidence: 92%
“…It will be interesting to investigate whether ACP2 and ACP5 also function as nucleotide phosphatases. It is perhaps significant that deficiency of these phosphatases is linked to inflammatory diseases [58,59], which we would predict arise from the resulting inhibition of PLD3 or PLD4 with attendant activation of nucleic acid sensors. In any case, some RNA virus genomes carry 5′-monophosphate [60], which may inhibit PLD3 and PLD4, possibly triggering downstream sensors for host innate immunity.…”
Section: Discussionmentioning
confidence: 99%